An unexpected diagnosis of adenomyosis in the subfertile woman. (27th February 2015) - Hunjan, Tia; Davidson, Andrew
Abstract : A 38-year-old nulliparous female presented to an assisted conception clinic with subfertility and a long-standing history of dysmenorrhoea. Transvaginal ultrasound revealed two lesions in the body of the uterus, which were presumed to be fibroids. A decision was made to remove these lesions prior to attempting in vitro fertilisation (IVF). However, on laparotomy, deeply penetrating adenomyosis was discovered, resulting in an unexpected hysterectomy and significant blood loss. Based on our experience, we highlight the importance of suspecting a diagnosis of adenomyosis preoperatively and the methods by which this diagnosis can be made, in order to avoid potential unforeseen outcomes as described in this case. We discuss conservative management options for this condition, particularly in women wishing to preserve fertility.